Electrically conducting flow through exponential power law fluid with variable thermal conductivity - Ferdows, Mohammad; Bangalee, M.Z.I.; Liu, Don (Zielona Góra: Uniwersytet Zielonogórski)
The problem of exponential law of steady, incompressible fluid flow in boundary layer and heat transfer are studied in an electrically conducting fluid over a semi-infinite vertical plate assuming the variable thermal conductivity in the presence of a uniform magnetic field. The governing system of equations including the continuity equation, momentum equation and energy equation have been transformed into nonlinear coupled ordinary differential equations using appropriate similarity variables.
Keywords: MHD; similarity solution; variable properties; boundary layer flow; exponential law